Library Research : Dewan Wanita dan CSR Menekan Earnings Management - Kadek Rahma Sari; Kartika Safira (Akuntansi, 2024)
This study aims to gather insights related to the relationship between gender diversity and CSR on earnings management actions in companies. The method used to obtain research results is library research, using credible and indexed sources on Scopus and Sinta. The results of this study indicate that first, gender diversity as measured by the presence of women on the composition of the board of directors can create conditions for management that are more ethical, intolerant and suppress opportunistic actions that encourage management to carry out earnings management. Second, CSR is an ethical act to blame the company in a transparent manner for stakeholders and is a form of corporate reputation for stakeholders thereby suppressing earnings management actions in the company.